Seasonal variations of fish diversity and species richness at the coastal water, Pekan, Pahang, Malaysia - John, Akbar; Khuraisha, N; Khan Chowdhury, Ahmed Jalal; Najiah, M; Nadirah, M (Noor Publishing, 2020)
This study was conducted from April 2019 to October 2019 to investigate the seasonal variations on fish diversity and species richness at coastal water Pekan, Pahang (Pantai Sepat, Cherok Paloh and Tanjung Selangor), Malaysia. A total of 5341 individual fishes were recorded which comprised 47 families and 108 species whereby 2444 individuals recorded during the non-monsoon season and 2897 individuals during the monsoon season. The most dominant families were Nemipteridae followed by Lutjanidae and Carangidae. The highest species richness was observed during the non-monsoon season with 95 species. Shannon-4 5 6$%! 5 ' -D), and Berger-Parker index were applied to demonstrate the species diversity, richness, evenness and dominance of fish in sampling areas and the overall values for non-monsoon season are 3.284, 0.9326 and 0.1335 respectively while for monsoon season are 2.766, 0.8798 and 0.2751 respectively. The high diversity index (Shannon-Weaver and Simpson) was observed in the non-monsoon season. This study has also demonstrated that the seasonal variations alone may not influence the number of species in a population along the coastal water Pekan. However, the status of fishing activities, collected fish species and water quality along the coastal water Pekan need to be monitored frequently for the sustainable harvesting of commercial species in coastal water of Pahang, Malaysia.